Acompañamiento familiar y logros de aprendizaje en el área de personal social en estudiantes del sexto grado de primaria de la Institución Educativa N° 60080, Caballococha 2024 - Pezo Juan de Dios, Danny Gabriel (2024)
The objective of this research was: Determine the relationship that exists between family support and the achievement of learning in the area of social personnel in students of the sixth grade of primary school of the Educational Institution No. 60080 of the city of Caballococha, during the year school year 2024. The research sample was 110 sixth grade primary school students. Hypothesis testing was performed using Spearman's Rho Correlation Test. The study allowed us to conclude that: there is a significant relationship between family support and learning achievements in the area of social personnel in the students of the sixth grade of primary school of the Educational Institution No. 60080 of Caballo Cocha during the 2024 school year, the level of family support in sixth grade students varies, with a medium level predominating (59.4%). The improvement between family support and learning achievements, with a high positive rating (Spearman's Rho = 0.916).